234k views
1 vote
I NEED HELP PLEASE, THANKS! :)

I NEED HELP PLEASE, THANKS! :)-example-1
User Matt Leach
by
5.1k points

2 Answers

4 votes

Answer:


\tan(4x)

Step-by-Step Explanation:

Notice that this resembles the difference identity for tangent. Specifically:


\displaystyle \tan(\alpha-\beta)=(\tan(\alpha)-\tan(\beta))/(1+\tan(\alpha)\tan(\beta))

So, given our equation, we can pretend that α=9x and β=5x. Therefore:


\displaystyle (\tan(9x)-\tan(5x))/(1+\tan(9x)\tan(5x))=\tan(9x-5x)=\tan(4x)

User Tassadaque
by
5.6k points
2 votes

Answer: tan(14x)

Explanation:

Consider the Sum Formula for tan:


tan(A + B)=(tan(A)+tan(B))/(1-tan(A)(tan(B))\\\\\\tan(9x+5x)=(tan(9x)+tan(5x))/(1-tan(9x)(tan(5x))\\\\\\\large\boxed{tan(14x)}=(tan(9x)+tan(5x))/(1-tan(9x)(tan(5x))

User Edthix
by
4.8k points